Equity research: Jerónimo Martins SGPS, SA - Almeida, Guilherme Alexandre Nunes de (2021)
The main objective of this dissertation is to carry out a global valuation of Jerónimo Martins and determine its value per share based on cash flows forecasts. In that sense, an analysis of the company was made, as well as a market study regarding the evolution of the retail industry. Jerónimo Martins SGPS is a Portuguese company, leader in the food retail market in Poland and one of the major players in the Portuguese market, beyond that it is also presence in the Colombian market. Jerónimo Martins also operates in the specialized retail, namely in cosmetics and confectionery markets and in the agribusiness industry. On 31/12/2020 Jerónimo Martins SGPS was listed on the Euronext Lisbon stock exchange and closed the year with a value of €13.82 per share. To determine the company value three valuation methods were used, the DCF, the EVA and the multiples methodology. According with the DCF model, the target price is €13.92, which represents an appreciation of 0.76% and thus the value offered by the market does not recognize the potential growth of the company. A sensitivity analysis was also performed to analyse the sensitivity of the share price to the discount rate and to the perpetual growth rate, two of the most crucial variables. In conclusion, it was done a comparative analysis of the results obtained through the several methods, which lead to a Buy recommendation, in line with the analysis carried out by CAIXA BANK.